The First Twenty Years of the Elca: Remembrances of a Retired Bishop - Maahs, Charles H. (Dialog, 2008)
The ELCA has experienced a number of significant events and developments in the first twenty years of its existence as a Church. In this article you will read about the preparation and direction that newly elected Bishops received for their ministry in their synods, and some of the struggles and joys that accompanied their work with one another and with their rostered leaders and congregations. It is the perspective of one retired Bishop Emeritus who gives an account of his ministry as he experienced it.